Lithium ion battery diaphragm containing bipyridine nitrogen, preparation method of lithium ion battery diaphragm and lithium ion battery

By introducing C2N into the lithium-ion battery separator to form an OPBI@C2N composite separator, the problems of thermal shrinkage of polyolefin separator and disorderly growth of lithium dendrites are solved, and the heat resistance and electrochemical performance of the separator are improved, which significantly improves the safety and electrochemical performance of the lithium-ion battery.

CN119601893APending Publication Date: 2025-03-11SHENZHEN ACAD OF METROLOGY & QUALITY INSPECTION +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411403611.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing polyolefin lithium-ion battery separators are prone to heat shrinkage at high temperatures, the lithium dendrites on the anode surface have severe disordered growth, poor high-temperature cycle stability, and the windows of conductivity, electrolyte wetting, flame retardant and electrochemical stability are not ideal.

Method used

The substrate was coated with OPBI@C2N mixed solution and the solvent was removed to prepare a lithium-ion battery separator containing bispyridine nitrogen. C2N is introduced into the battery separator to improve the diffusion force during the non-solvent phase conversion method, and form a microscopic pore structure of regular, dense and orderly finger-like pores and sponge-like pores.

Benefits of technology

The separator has excellent heat resistance, flame retardancy and electrochemical stability, inhibits the disorderly growth of lithium dendrites, improves the safety and electrochemical performance of lithium-ion batteries, and shows excellent discharge specific capacity, cycle stability and rate performance, especially at high temperatures to charge and discharge stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601893A_ABST
    Figure CN119601893A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion batteries, in particular to a lithium ion battery diaphragm containing bipyridine nitrogen, a preparation method of the lithium ion battery diaphragm and a lithium ion battery, and the preparation method comprises four steps which are shown in Figure 1 in Figure 1 in Figure 1 in the specification. According to the invention, C2N is introduced into the battery diaphragm, and the diffusive force in the nonsolvent phase inversion process is changed by C2N, so that the high-temperature-resistant lithium ion battery diaphragm (OPBI-C2N) of which the microscopic pore channel structure consists of regular, dense and ordered finger-shaped pores and spongy pores is obtained. The diaphragm can effectively inhibit disordered growth of lithium dendrites and improve the safety of the lithium ion battery; the diaphragm contains a bispyridine nitrogen structure, provides additional active sites for lithium ion transmission and storage, and is beneficial to rapid transportation of lithium ions; the diaphragm electrolyte is good in wettability and electrochemical stability, and the assembled battery shows excellent specific discharge capacity, cycling stability and rate capability, and especially has excellent charge-discharge stability at high temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a lithium ion battery separator containing bipyridine nitrogen and a preparation method thereof, and a lithium ion battery. Background Art

[0002] The separator is one of the core components of lithium-ion batteries (LIBs). Its function is to separate the positive electrode from the negative electrode to prevent the battery from short-circuiting and causing safety accidents. At the same time, it provides a microporous channel for lithium ions to shuttle between the positive and negative electrodes during charging and discharging. The performance of the separator directly affects the safety, capacity, rate, life and other performance of the battery.

[0003] Polyolefin separators, such as polyethylene (PE) separators, polypropylene (PP) separators, and PE / PP composite films, are the mainstream products in the current separator market, and the production processes are mainly dry and wet. Due to the limitations of material properties and production processes, polyolefin separators still face several problems in the application process: First, the melting point of polyolefin materials is low, so polyolefin separators have poor heat resistance and are prone to thermal shrinkage at high temperatures, which can lead to battery short circuits, and then cause dangerous events such as lithium battery fires and explosions; second, the conductivity, electrolyte wettability, flame retardancy, and electrochemical stability window of polyolefin separators are not ideal; third, the lithium dendrites of batteries assembled with polyolefin separators grow severely during service, and lithium dendrites can easily pierce the separator, causing micro-short circuits in lithium batteries, causing safety hazards to lithium batteries; fourth, the cycle stability of batteries assembled with polyolefin separators at high temperatures (such as 90°C) is very poor.

[0004] In order to improve the safety of use and electrochemical performance of lithium batteries, some materials are coated on the surface of polyolefin diaphragms through different coating processes to form coated polyolefin diaphragms; the coated diaphragms on the market mainly include inorganic coated diaphragms, organic coated diaphragms, and organic + inorganic coated diaphragms. The coating materials used in this type of coated diaphragms usually have good heat resistance. However, the base material under the coating often shrinks at high temperatures, resulting in the collapse of the overall structure of the diaphragm. Therefore, this modification scheme based on polyolefin diaphragms cannot fundamentally solve the problem of heat resistance of the diaphragm, and cannot fundamentally solve the safety of lithium batteries. In addition, the growth of anode lithium dendrites in lithium batteries assembled with this type of coated polyolefin diaphragm is still relatively serious during the charge and discharge cycle. As we all know, coating also causes some negative effects, such as increased diaphragm thickness and body resistance (R b ) increases, the charge / discharge efficiency decreases, etc.

[0005] Therefore, the prior art still needs to be improved and developed. Summary of the invention

[0006] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide a lithium-ion battery separator containing bipyridine nitrogen and a preparation method thereof, and a lithium-ion battery, aiming to solve the following problems: the existing polyolefin separators are prone to thermal shrinkage at high temperatures; the lithium dendrites on the anode surface of the lithium-ion battery assembled with the existing polyolefin separators have serious disordered growth; the lithium-ion battery assembled with the existing polyolefin separators has poor high-temperature cycle stability; the electrical conductivity, electrolyte wettability, flame retardancy, electrochemical stability window, etc. of the polyolefin separators are not ideal.

[0007] The technical solution of the present invention is as follows:

[0008] A method for preparing a lithium ion battery separator containing bipyridinium nitrogen comprises the following steps:

[0009] Providing an OPBI solution and a solution containing C2N;

[0010] The OPBI solution and the C2N-containing solution are mixed to obtain an OPBI@C2N mixed solution;

[0011] The OPBI@C2N mixed solution is coated on a substrate, and the solvent in the OPBI@C2N mixed solution is removed to obtain a lithium ion battery separator containing bipyridine nitrogen.

[0012] The method for preparing a lithium-ion battery separator containing bipyridine nitrogen, wherein the solvent of the solution containing C2N and the solvent of the OPBI solution are jointly selected from one or more of N-methylpyrrolidone, dimethyl sulfoxide, and N,N-dimethylacetamide.

[0013] The method for preparing the bipyridinium nitrogen-containing lithium-ion battery separator, wherein the mass proportion of C2N in the OPBI@C2N mixed solution is 0.2%-0.9%.

[0014] The method for preparing the bipyridinium nitrogen-containing lithium-ion battery separator, wherein in the preparation process of C2N, a dichloromethane solution of the precursor HAT-CN is mixed with NaCl and then sintered at high temperature under the protection of an inert gas.

[0015] The method for preparing a lithium-ion battery separator containing bipyridinic nitrogen is characterized in that the high temperature is 400-1000°C.

[0016] The method for preparing the bipyridinium nitrogen-containing lithium-ion battery separator, wherein the mixing treatment is continuous stirring at room temperature for 15-24 hours.

[0017] The method for preparing the bipyridinium nitrogen-containing lithium-ion battery separator, wherein the method for removing the solvent in the mixed solution is: placing the substrate coated with the mixed solution in anhydrous methanol for immersion treatment, and the immersion treatment is standing at room temperature for 8-15 minutes.

[0018] A lithium ion battery separator containing bipyridinium nitrogen is prepared by using the preparation method of the lithium ion battery separator (non-solvent phase transfer method).

[0019] The bipyridinium nitrogen-containing lithium-ion battery separator has a thickness of 15-40 microns.

[0020] A lithium ion battery comprises a positive electrode sheet, a negative electrode sheet and a lithium ion battery separator containing bipyridinic nitrogen; the lithium ion battery separator containing bipyridinic nitrogen is located between the positive electrode sheet and the negative electrode sheet.

[0021] Beneficial effects: The present invention provides a lithium ion battery separator containing bipyridinyl nitrogen and a preparation method thereof, and a lithium ion battery. The preparation method comprises the following steps: providing an OPBI solution and a solution containing C2N; mixing the OPBI solution and the solution containing C2N to obtain an OPBI@C2N mixed solution; coating the OPBI@C2N mixed solution on a substrate, and removing the solvent in the mixed solution to obtain a lithium ion battery separator containing bipyridinyl nitrogen; and assembling a lithium ion battery using the lithium ion battery separator containing bipyridinyl nitrogen. The present invention introduces C2N into the battery separator, and C2N has abundant nitrogen active sites and a two-dimensional structure, which is beneficial to the transport of lithium ions; at the same time, C2N is used to change the diffusion force in the non-solvent phase conversion process to obtain a high temperature resistant lithium ion battery separator whose microscopic pore structure is composed of regular, dense and orderly finger-like pores and sponge-like pores, and the unique microscopic pore structure is also beneficial to the transport of lithium ions. The membrane electrolyte has good wettability, high conductivity, and good electrochemical stability. The unique microscopic pore structure can induce lithium ions to pass through the membrane more quickly and deposit evenly on the surface of the lithium metal anode, effectively inhibiting the disordered growth of lithium dendrites and improving the safety and electrochemical performance of lithium-ion batteries. The battery assembled using this membrane exhibits excellent discharge capacity, cycle stability, and rate performance. More importantly, the excellent heat resistance of OPBI and C2N ensures the excellent charge and discharge stability of the assembled battery at high temperatures, effectively preventing safety accidents caused by internal short circuits in the battery due to the physical size shrinkage of the membrane at high temperatures. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The figure is a schematic flow chart of a method for preparing a lithium-ion battery separator containing bipyridinium nitrogen according to the present invention;

[0023] Figure 2 is a flow chart for the preparation of C2N;

[0024] Figure 3 Physical characterization of C2N [(a) XPS survey spectrum of C2N, (bd) high-resolution spectra of N1s, C 1s and O1s, (e) C2N structure diagram, (f) XRD spectrum of C2N powder sample, (g) SEM image of C2N powder sample, (h) TEM structure diagram of C2N sample];

[0025] Figure 4 is the adsorption energy between lithium ions and C2N calculated under solution conditions [(a) adsorption energy between nitrogen structure molecules in OPBI and lithium ions, (b) adsorption energy between nitrogen structure molecules in C2N and lithium ions];

[0026] Figure 5 SEM images of the upper and lower surfaces and cross-sections of PP, OPBI, and OPBI@C2N separators;

[0027] Figure 6 Results of (a) heat resistance, (b) thermal weight loss curve, and (c) flame retardancy of PP film, OPBI film, and OPBI@C2N composite film;

[0028] Figure 7 Comparison of (a) surface pore distribution digital photos, (b) contact angle with electrolyte, (c) surface pore volume, (d) porosity and electrolyte absorption rate of PP membrane, OPBI membrane and OPBI@C2N composite membrane;

[0029] Figure 8 Analysis of the mechanical properties and electrochemical stability of the separator [(a) folding, bending and recovery treatment of OPBI@C2N separator, (b) stress-strain curve of the separator, (c) Nyquist curve of Li / separator / Li battery, (d) LSV curve of the separator, (e) AC impedance curve of double steel sheet symmetric battery];

[0030] Fig. 9 Cycling stability and rate performance of the battery [(a) Cycling performance of LFP / Li half-cell at 25°C and 0.5C, (b) Rate performance of LFP / Li half-cell, (c) SEM image of the anode surface of LFP / Li half-cell after 200 cycles];

[0031] Fig.10 Cyclic discharge performance of LiFP / Li battery assembled with PP membrane and OPBI@C2N composite membrane at 90°C. DETAILED DESCRIPTION

[0032] The present invention provides a lithium ion battery separator containing bipyridinium nitrogen and a preparation method thereof, and a lithium ion battery. In order to make the purpose, technical scheme and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0033] It will be understood by those skilled in the art that, unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as generally understood by those skilled in the art in the art to which the present invention belongs. It should also be understood that terms such as those defined in general dictionaries should be understood to have meanings consistent with the meanings in the context of the prior art, and will not be interpreted with idealized or overly formal meanings unless specifically defined as herein.

[0034] like Figure 1 As shown, the present invention provides a method for preparing a lithium ion battery separator containing bipyridine nitrogen and a lithium ion battery, comprising the steps of:

[0035] Step S10: providing an OPBI solution and a solution containing C2N;

[0036] Step S20: mixing the OPBI solution and the C2N-containing solution to obtain an OPBI@C2N mixed solution;

[0037] Step S30: coating the OPBI@C2N mixed solution on a substrate, and removing the solvent in the OPBI@C2N mixed solution to obtain a lithium-ion battery separator containing bipyridine nitrogen;

[0038] Step S40: Assembling a lithium-ion battery using the lithium-ion battery separator containing bipyridine nitrogen. In this embodiment, polybenzimidazole (OPBI) is a polymer with excellent thermal stability and mechanical properties. Since the OPBI molecular chain contains polar ether bonds and pyridine structures, it can enhance the affinity with the electrolyte. Therefore, it is prepared into a polymer separator for lithium-ion batteries, which can improve the safety and electrochemical performance of the battery. As a special member of the nitrogen-doped carbon family, C2N has abundant nitrogen active sites, clear carbon-nitrogen covalent structures, and precisely arranged pore structures, all of which are conducive to the conduction and storage of lithium ions. Many studies have shown that there is a strong interaction between the nitrogen-containing C2N monolayer and lithium ions, which can improve the electrochemical performance of lithium-ion batteries. At the same time, as a carbonitride material, C2N has excellent high temperature resistance, can maintain structural stability under high temperature conditions and exhibit good antioxidant properties. The OPBI@C2N mixed solution was configured, and the OPBI@C2N composite separator was prepared by a non-solvent induced phase separation (NIPS) process.

[0039] Specifically, in view of the characteristics of polybenzimidazole and C2N, the two are composited into a lithium-ion battery separator and applied to lithium-ion batteries, which helps to solve the safety problems of lithium-ion batteries caused by the heat resistance, flammability and disordered growth of lithium dendrites of the separator. At the same time, the electrochemical properties of lithium-ion batteries such as rate and cycle stability (including room temperature and high temperature) are improved from the perspective of the separator. Experimental data show that compared with commercial polyolefin separators, the lithium-ion battery composite separator prepared by the non-solvent phase separation process has excellent heat resistance, flame retardancy and the effect of inhibiting the disordered growth of lithium dendrites, which can effectively improve the safety of lithium-ion batteries. At the same time, the lithium-ion battery separator exhibits higher ionic conductivity ( 0.95 mxD -1 ) and electrolyte absorption rate (597.7%). After the LiFePO4 / Li battery assembled with the lithium-ion battery separator is charged and discharged 200 times at 0.5C, the capacity retention rate of the battery is 91.6%. In addition, the LiFePO4 / Li battery assembled with the lithium-ion battery separator can also operate at a temperature of 90°C and has a considerable capacity retention rate.

[0040] In some embodiments, the solvent of the C2N-containing solution and the solvent of the OPBI solution are jointly selected from but not limited to one or more of N-methylpyrrolidone (NMP), dimethyl sulfoxide (DMSO), and N,N-dimethylacetamide; the solvents of the C2N-containing solution and the OPBI solution are ensured to be consistent, so as to facilitate the subsequent non-solvent induced separation process.

[0041] In some embodiments, in the mixed solution, the mass proportion of the C2N is 0.2%-0.9%; the lithium-ion battery separator can contain an appropriate amount of C2N, so that C2N can be used to improve the diffusion force during the non-solvent phase transformation method to obtain a high-temperature resistant lithium-ion battery separator (OPBI@C2N) with a microscopic pore structure composed of regular, dense and orderly finger-like pores and sponge-like pores.

[0042] In a preferred embodiment, in the mixed solution, the ratio of the mass of OPBI to the volume of the solvent of the mixed solution is 1 g:(9-11) ml, but is not limited thereto; specifically, it can also be 1 g:10 ml. In a preferred embodiment, the C2N is a two-dimensional nanosheet structure; the solution containing C2N is a C2N solution with N-methylpyrrolidone as solvent; the solvent of the OPBI solution is N-methylpyrrolidone; since polybenzimidazole has excellent thermal stability, mechanical properties, flame retardancy, etc., C2N has excellent thermal stability, large specific surface area, good stability, etc., and because it has abundant nitrogen active sites, clear carbon-nitrogen covalent structure, and precisely arranged pore structure, it is beneficial to the transport and storage of lithium ions; therefore, in view of the material characteristics of polybenzimidazole and C2N, the two are composited into a diaphragm for application in lithium-ion batteries, which helps to solve the safety problems of lithium-ion batteries caused by the heat resistance, flammability and disordered growth of lithium dendrites of the diaphragm, and at the same time improve the electrochemical properties of lithium-ion batteries such as rate, cycle stability (including room temperature and high temperature) from the perspective of the diaphragm.

[0043] In some embodiments, the mixing treatment is continuous stirring at room temperature for 15-24 hours; stirring at room temperature for 15-24 hours allows OPBI and C2N to be evenly mixed, in preparation for obtaining a lithium-ion battery separator with better performance.

[0044] In some embodiments, in step S30, the method for removing the solvent in the mixed solution is: placing the substrate coated with the mixed solution in anhydrous methanol for immersion treatment, the immersion treatment is standing at room temperature for 8-15 minutes, and preparing the lithium ion battery separator by non-solvent induced phase separation process. Since OPBI is insoluble in methanol, C2N is also insoluble in methanol at room temperature, and NMP or DMSO or DMAC is soluble in methanol, the substrate coated with the mixed solution is stood at room temperature for 8-15 minutes, and methanol is used to make the mixed solution quickly form a film, and replace NMP or DMSO or DMAC to form pores, so that the prepared lithium ion battery separator has a microscopic pore structure composed of regular, dense and orderly finger-like pores and sponge-like pores, which is conducive to the rapid transport of lithium ions between the positive and negative electrodes and the uniform deposition on the anode surface, thereby improving the electrochemical performance of the battery and inhibiting the disordered growth of lithium dendrites, thereby improving the electrochemical performance and safety of the battery during service.

[0045] In some embodiments, in step S30, after the soaking treatment, a drying treatment is further performed to remove methanol in the pores.

[0046] In some embodiments, the substrate is, but is not limited to, a glass plate.

[0047] In addition, the present invention also provides a lithium ion battery separator, which is prepared by using the preparation method of the lithium ion battery separator containing bipyridine nitrogen.

[0048] In this embodiment, C2N is introduced into the lithium-ion battery separator, and C2N is used to improve the diffusion force during the non-solvent phase conversion method to obtain a high-temperature resistant lithium-ion battery separator (OPBI@C2N) whose microscopic pore structure is composed of regular, dense and orderly finger-like pores and sponge-like pores. The lithium-ion battery separator has excellent thermal stability and excellent flame retardancy, no thermal shrinkage occurs at 200°C, and no obvious combustion phenomenon occurs when placed on a flame; the lithium-ion battery separator has good electrolyte wettability, a large electrolyte absorption rate (597.7%), and high conductivity (0.95mS cm -1 ), good electrochemical stability; the lithium-ion battery separator has a unique microscopic pore structure composed of regular, dense and orderly finger-like pores and sponge-like pores, which can induce lithium ions to pass through the separator more quickly and deposit evenly on the surface of the lithium metal anode, effectively inhibit the disordered growth of lithium dendrites, and improve the safety and electrochemical performance of lithium-ion batteries. The battery assembled using the separator exhibits excellent discharge specific capacity, cycle stability, and rate performance, especially excellent charge and discharge stability at high temperatures.

[0049] In some embodiments, the bipyridinium nitrogen-containing lithium-ion battery separator has a thickness of 25-40 microns; the lithium-ion battery separator at this thickness has excellent thermal stability and can inhibit the disordered growth of lithium dendrites.

[0050] In addition, the present invention also provides a lithium-ion battery, including a positive electrode sheet, a negative electrode sheet and a lithium-ion battery separator containing bipyridinic nitrogen; the lithium-ion battery separator containing bipyridinic nitrogen is located between the positive electrode sheet and the negative electrode sheet.

[0051] In this embodiment, after the LiFePO4 / Li battery assembled with the lithium ion battery separator containing bipyridinyl nitrogen is charged and discharged 200 times at 0.5C, the battery capacity retention rate is 91.6%. In addition, the LiFePO4 / Li battery assembled with the lithium ion battery separator containing bipyridinyl nitrogen can also operate at a temperature of 90°C and have a considerable capacity retention rate; and the battery assembled with the lithium ion battery separator containing bipyridinyl nitrogen can operate smoothly and safely at high temperatures (such as 90°C).

[0052] The following examples are further given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention.

[0053] Example 1

[0054] This embodiment provides a method for preparing a lithium-ion battery separator containing bipyridinium nitrogen (OPBI@C2N composite membrane) and a lithium-ion battery, and its flow diagram is shown in FIG. Figure 1 As shown, the steps include:

[0055] Step S1: dissolving OPBI in NMP to form a uniform OPBI solution;

[0056] C2N is dissolved in NMP to form a C2N solution with NMP as solvent (C2N accounts for 25 mg / ml), namely, a C2N solution.

[0057] Step S2: Add the C2N solution to the OPBI solution and continue stirring at room temperature for 20 hours to obtain a mixed solution, in which the ratio of OPBI:NMP is 1 g:10 ml.

[0058] Step S3: The obtained OPBI@C2N mixed solution was coated on a glass plate with a scraper and transferred into anhydrous methanol (MeOH) for 10 min to obtain a porous film, and then the porous film was dried at room temperature to obtain an OPBI@C2N composite film.

[0059] Step S4: assembling a lithium-ion battery using the lithium-ion battery separator containing bipyridinic nitrogen.

[0060] The schematic diagram of the preparation process of C2N is as follows: Figure 2 As shown. First, 100 mg of HAT-CN was dispersed in 10 mL of dichloromethane and then stirred for 30 min under magnetic stirring. Next, the precursor dispersion was compounded with 600 g of sodium chloride crystals and continuously manually shaken. Then, it was dried at 80 °C. After that, the composite was placed in a tube furnace and heated at a flow rate of 100 mL min -1 The temperature was raised from room temperature to 550 °C and maintained for 2 h to complete the polymerization. Finally, the product was freeze-dried for 48 h for further study and polymerization. Finally, the product was washed with a large amount of deionized water to completely remove the NaCl template.

[0061] For comparison, this embodiment also provides a PP (polypropylene) film and an OPBI film, wherein the preparation method of the OPBI film is the same as the preparation method of the OPBI@C2N composite film, both of which adopt a non-solvent phase transfer method.

[0062] The chemical composition and micromorphology of the C2N material were characterized as follows:

[0063] Figure 3The physical properties of C2N are characterized [(a) XPS survey spectrum of C2N, (bd) high-resolution spectra of N1s, C 1s and O1s, respectively, (e) C2N structure diagram, (f) XRD spectrum of C2N powder sample, (g) SEM image of C2N powder sample, (h) TEM structure diagram of C2N sample]. Combined with the above characterization results, it can be concluded that the C2N material was successfully prepared in this experiment.

[0064] The adsorption energy between C2N and lithium ions is characterized as follows:

[0065] Figure 4 The adsorption energy between lithium ions and C2N calculated under solution conditions [(a) adsorption energy between nitrogen structure molecules in OPBI and lithium ions, (b) adsorption energy between nitrogen structure molecules in C2N and lithium ions]. Taking OPBI and C2N as the two molecules, the effects of different types of pyridine nitrogen structures on the lithium ion adsorption performance were explored. The lone pair electrons on the pyridine nitrogen structure have a strong adsorption effect on lithium ions. The pyridine nitrogen structure in the OPBI molecule exists in the form of an imidazole ring, while the C2N molecule uses the nitrogen atom in the pyridine ring with aromatic properties as the main adsorption site. These different types of pyridine nitrogen structures show different lithium ion adsorption capabilities. The adsorption energy calculation results show that the adsorption energy of the pyridine nitrogen structure in OPBI for lithium ions is -0.1eV, while the adsorption energy of the pyridine nitrogen structure in C2N for lithium ions is -0.158eV. These negative adsorption energy values ​​indicate that the interaction between the pyridine nitrogen structure and lithium ions is exothermic, that is, the adsorption of lithium ions by the pyridine nitrogen structure is a stable and favorable process. In addition, pyridine molecules have a large surface area and pore structure, which creates conditions for providing more adsorption sites and also enhances the adsorption capacity of lithium ions. Pyridine molecules have a stable structure, good chemical stability and electrochemical properties, and have potential application prospects in lithium-ion batteries and other fields.

[0066] The microscopic morphology of PP film, OPBI film and OPBI@C2N composite film was characterized as follows:

[0067] Figure 5 The SEM images of the upper and lower surfaces and cross sections of PP, OPBI and OPBI@C2N separators are shown in Figure 2. Figure 5It can be seen that the pore distribution of the diaphragm prepared by the NIPS method is more uniform and dense than that of the PP diaphragm, which helps to improve the adsorption capacity of the diaphragm to the electrolyte and effectively reduce the loss of the electrolyte. Secondly, C2N improves the diffusion force during the non-solvent phase transformation method, so that the OPBI@C2N composite membrane has a microscopic pore structure composed of regular, dense and orderly finger-like pores and sponge-like pores. This structural regulation helps the rapid transport of lithium ions between the positive and negative electrodes and the uniform deposition on the anode surface, thereby effectively improving the electrochemical performance of the battery and inhibiting the random growth of lithium dendrites. In summary, the OPBI@C2N composite membrane exhibits more superior microstructural characteristics than the PP membrane and OPBI membrane. These characteristics provide important support for improving the performance and cycle stability of lithium-ion batteries.

[0068] The thermal stability and flame retardancy of PP film, OPBI film and OPBI@C2N composite film were characterized as follows:

[0069] Figure 6 The results of (a) heat resistance, (b) thermal weight loss curve, and (c) flame retardancy of PP film, OPBI film, and OPBI@C2N composite film are shown. At different temperatures, the performances of PP film, OPBI film, and OPBI@C2N membrane are different. Specifically, the PP film shows edge shrinkage at 150°C and completely melts at 200°C; in contrast, the OPBI membrane and OPBI@C2N membrane show almost no shrinkage after being placed at 200°C for 1 hour, showing excellent high-temperature dimensional stability. In addition, Figure 6 As shown in Figure b, the initial decomposition temperatures of the OPBI membrane and the OPBI@C2N membrane are as high as 496°C, and the weight loss rate is about 4.3%, which is much higher than the initial decomposition temperature of the PP membrane (315°C). The weight loss of the OPBI and OPBI@C2N membranes at 220°C is mainly due to the volatilization of the residual solvent (NMP) in the membrane and has nothing to do with the decomposition of the membrane. At 470°C, the PP membrane is completely decomposed, while the OPBI and OPBI@C2N membranes still retain 88.1% and 90.2% of their mass at 600°C, showing excellent inherent thermal stability. Compared with the OPBI membrane, the dimensional stability and thermal stability of the OPBI@C2N membrane are particularly outstanding.

[0070] The PP film, OPBI film, and OPBI@C2N composite film were cut into small rectangles of 2×3 cm for flame retardancy tests. The PP diaphragm shrinks rapidly when it is close to the flame and burns immediately once it comes into contact with the flame. Even after leaving the flame, the PP diaphragm continues to burn. In contrast, the OPBI diaphragm only shrinks when it is about to come into contact with the flame. When it comes into contact with the flame, it quickly "carbonizes" after contact with the flame, effectively preventing further combustion and showing good flame retardant properties. This shows that OPBI has good flame retardant properties and can effectively prevent the spread of fire. The phenomenon of OPBI@C2N diaphragm is similar to that of OPBI diaphragm, but its shrinkage phenomenon when very close to the flame is not very significant. This is because C2N has excellent thermal stability, can maintain structural stability in high temperature environments, and has the ability to prevent the spread of fire. Overall, the OPBI@C2N diaphragm exhibits better flame retardant properties and can effectively inhibit the occurrence and spread of fire.

[0071] The surface pore distribution, porosity, pore volume, electrolyte absorption rate and contact angle of PP membrane, OPBI membrane and OPBI@C2N composite membrane were characterized as follows:

[0072] Figure 7 Comparison of (a) surface pore distribution digital photos, (b) contact angle with electrolyte, (c) surface pore volume, (d) porosity and electrolyte absorption rate of PP membrane, OPBI membrane and OPBI@C2N composite membrane. The electrolyte wettability of the diaphragm has a significant impact on the performance and stability of the battery. Good electrolyte wettability helps to ensure that the electrolyte is evenly distributed on both sides of the diaphragm, reduce internal resistance, and prevent chemical substances from gathering on the diaphragm, thereby improving the life and stability of the battery. The absorption rate of the diaphragm to the electrolyte is closely related to the surface pore volume of the diaphragm. Figure 7 As shown in a, the surface pore volume of various types of membranes is calculated based on the total volume of pores on the material surface and the surface area of ​​the material. Obviously, the OPBI@C2N membrane shows a higher surface pore volume, which means that there are more tiny pores on the membrane surface that can accommodate liquid, increasing the contact area between the liquid and the membrane material surface and improving its wettability. Secondly, Figure 7 As shown in Fig. 2b, the contact angle between the OPBI@C2N membrane and the electrolyte is 15.64°, which is significantly smaller than the contact angle of the PP film (50.84°). This is not only due to the high porosity and high surface pore volume of the OPBI@C2N membrane, but also because the bipyridine nitrogen structure in the OPBI and C2N structures has good electrolyte absorption performance, which makes the membrane have a good affinity for the electrolyte. To further verify that the OPBI@C2N membrane has a good affinity for the electrolyte, the porosity and electrolyte absorption rate of the membrane were calculated, as shown in Fig. Figure 7d. The OPBI@C2N membrane has a porosity of up to 65.97%, which is significantly higher than that of the PP and OPBI membranes. Secondly, the electrolyte absorption rates of the PP, OPBI and OPBI@C2N membranes are 62.9%, 490.6% and 597.7%, respectively. This further illustrates that the OPBI@C2N membrane ensures good electrolyte wettability through its excellent pore structure, surface pore volume and electrolyte absorption performance, which helps to improve the performance and stability of the battery.

[0073] The mechanical properties and electrochemical stability of the diaphragm were characterized as follows:

[0074] Figure 8 Analysis of the mechanical properties and electrochemical stability of the separator [(a) folding, bending and recovery of OPBI@C2N separator, (b) stress-strain curve of the separator, (c) Nyquist curve of Li / separator / Li battery, (d) LSV curve of the separator, (e) AC impedance curve of double steel sheet symmetrical battery]. To ensure that the separator has good stability and reliability during use, the separator needs to have good mechanical properties. Figure 8 As shown in Figure a, no rupture was observed after the OPBI@C2N separator was folded or bent, indicating that the separator has good anti-bending ability, which is beneficial to ensure the integrity of the separator during battery assembly. Figure 8 The stress-strain curve shown in b shows the mechanical behavior of the diaphragm, and by comparing the tensile strength TS values, it is found that the mechanical properties of the OPBI diaphragm and the OPBI@C2N diaphragm are relatively low, and there is a significant gap compared with the commercial PP diaphragm. This is mainly attributed to the different film-forming processes. The commercial PP diaphragm uses extrusion, stretching and other processes to optimize the molecular structure of the material and improve the mechanical properties; the OPBI and OPBI@C2N diaphragms are prepared by the NIPS process, resulting in uneven structure, unsatisfactory polymer chain arrangement, and unreasonable pore structure, resulting in low mechanical properties. Although the OPBI and OPBI@C2N diaphragms have low mechanical properties, they are still reliable during battery operation and are not easily punctured by lithium dendrites, which helps to ensure the normal assembly and operation of the battery. Therefore, the mechanical properties of the diaphragm need to be taken into account in battery design to ensure the stability and reliability of the battery.

[0075] The performance of PP, OPBI and OPBI@C2N separators in Li / Li symmetric batteries was evaluated by Nyquist plots. Figure 8 As shown in Figure c, the OPBI@C2N separator exhibits the best interfacial compatibility in the Li / Li symmetric battery, and its impedance is the smallest, indicating that it has the best compatibility with lithium metal. Then, the electrochemical stability of PP, OPBI, and OPBI@C2N separators was studied and analyzed through LSV testing. Figure 8As shown in (d), the OPBI@C2N separator exhibits excellent anodic stability in the electrochemical window up to 5.2 V. In contrast, the PP separator has a poor anodic stability in the Li + / Li voltage was about 4.5V, and current fluctuations occurred, indicating that OPBI@C2N has a high electrochemical stability window. The excellent performance of OPBI@C2N membrane in the above two tests is attributed to its high porosity and surface pore volume, which is conducive to the rapid filling of electrolyte and provides a superior transmission environment in lithium-ion batteries. In addition, the presence of two pyridine nitrogen structures in the OPBI@C2N composite membrane effectively neutralizes the acidic substances produced in the battery reaction, thereby ensuring stability at the anode interface. Therefore, in terms of anode stability, OPBI@C2N membrane has excellent performance.

[0076] The ionic conductivity of the membrane, also known as ionic conductivity, refers to the conductivity of the ionic current per unit area through the membrane. The ionic conductivity of the membrane mainly depends on the structure and properties of the material. Figure 8 As shown in Figure e, the Rb of the separator is measured by the SS / separator / SS battery, and the conductivity of each type of separator is calculated according to the calculation formula. The conductivity of the OPBI@C2N separator is 0.95mS cm -1 , which is significantly higher than that of PP diaphragm (0.44mS cm -1 ) and OPBI membrane (0.68 mS cm -1 ). This can be attributed to the good charge transfer performance of its pyridine nitrogen structure: the pyridine nitrogen atom has a high electronegativity, has the ability to attract the surrounding positively charged ions, and can form hydrogen bonds or ionic bonds with negative ions, thereby promoting the ion transfer rate in the separator. In addition, the porosity of the separator and the good solvent compatibility of the pyridine nitrogen structure also provide advantages for its good electrolyte absorption capacity, which is conducive to the transmission of lithium ions. In contrast, the ionic conductivity of the PP separator and the OPBI separator is significantly lower, which is related to the limitations of their material structure and properties. Therefore, by rationally designing a structure with good ion conductivity in the separator, such as the pyridine nitrogen structure, the ionic conductivity of the separator can be significantly improved, thereby improving the battery performance.

[0077] The cycle stability and rate performance of the battery are characterized as follows:

[0078] Fig. 9 The cycling stability and rate performance of the battery [(a) cycling performance of LFP / Li half-cell at 25°C and 0.5C, (b) rate performance of LFP / Li half-cell, (c) SEM image of the anode surface of LFP / Li half-cell after 200 cycles]. Fig. 9As shown in a, within the initial 25 cycles, the discharge capacity values ​​of the batteries assembled with the three separators were similar. However, starting from the 26th cycle, the discharge capacity of the battery assembled with the PP separator began to decline significantly. At the same time, the batteries assembled with the OPBI separator and the OPBI@C2N separator also experienced a decline in capacity, among which the capacity of the battery assembled with the OPBI@C2N separator decreased the slowest. After 200 cycles, the discharge capacity of the batteries assembled with the PP, OPBI, and OPBI@C2N separators was 78.57 mAh g -1 、95.5mAh g -1 and 130.78mAh g -1 . According to calculations, it can be concluded that the capacity retention rates of the above three batteries are 57.1%, 68.7% and 91.6%, respectively. This difference is mainly attributed to the combined effects of the microscopic pore structure of the diaphragm, the wettability of the electrolyte, and the composition of the diaphragm. The OPBI@C2N diaphragm has a microscopic pore structure composed of regular, densely ordered finger-like pores and sponge-like pores, good electrolyte wettability, and more importantly, the two pyridine nitrogen structures in the OPBI@C2N diaphragm provide additional active sites for lithium ion transmission and storage, thereby increasing the lithium ion transmission rate, inhibiting irreversible reactions in the cycle, reducing capacity loss and slowing down the decline in cycle life. Therefore, compared with PP diaphragms and OPBI diaphragms, the battery assembled with the OPBI@C2N diaphragm has the best cycle stability. Fig. 9 As shown in Figure b, compared with PP separator and OPBI separator, the battery assembled with OPBI@C2N separator has the best discharge rate performance, which is also attributed to the unique microscopic pore structure of OPBI@C2N separator, good electrolyte wettability and the contained bipyridine nitrogen structure.

[0079] The high temperature discharge performance of LiFP / Li battery assembled with PP film and OPBI@C2N composite film was characterized as follows:

[0080] Fig.10 The cyclic discharge performance of LiFP / Li battery assembled with PP membrane and OPBI@C2N composite membrane at 90°C. Obviously, compared with PP separator, LiFP / Li battery assembled with OPBI@C2N composite membrane showed better cycle stability and safety under the test conditions of 90°C and 0.5C, which is mainly attributed to the excellent heat resistance, unique microscopic pore structure, good electrolyte wettability and bipyridine nitrogen structure contained in OPBI@C2N composite membrane.

[0081] In summary, the present invention provides a lithium ion battery separator containing bipyridinyl nitrogen and a preparation method thereof, and a lithium ion battery. The preparation method comprises the steps of: providing an OPBI solution and a solution containing C2N; mixing the OPBI solution and the solution containing C2N to obtain an OPBI@C2N mixed solution; coating the OPBI@C2N mixed solution on a substrate, and removing the solvent in the OPBI@C2N mixed solution to obtain a lithium ion battery separator containing bipyridinyl nitrogen; and assembling a lithium ion battery using the lithium ion battery separator containing bipyridinyl nitrogen. The present invention introduces C2N into the battery separator and utilizes C2N to improve the diffusion force in the non-solvent phase conversion process to obtain a high-temperature resistant lithium-ion battery separator (OPBI@C2N) whose microscopic pore structure is composed of regular, dense and orderly finger-like pores and sponge-like pores. This unique pore structure can induce lithium ions to pass through the separator more quickly and deposit evenly on the surface of the lithium metal anode, effectively inhibiting the disordered growth of lithium dendrites and improving the safety and electrochemical performance of lithium-ion batteries. In addition, the OPBI@C2N composite separator contains a bipyridine nitrogen structure, which provides additional active sites for lithium ion transmission and storage, helps the rapid transport of lithium ions, inhibits irreversible reactions in the cycle, reduces capacity loss and slows down the decline in cycle life. The OPBI@C2N composite separator has good electrolyte wettability, high conductivity and good electrochemical stability. The battery assembled using the separator exhibits excellent discharge specific capacity, cycle stability and rate performance, especially excellent charge and discharge stability at high temperature.

[0082] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.

Claims

1. A method for preparing a lithium ion battery separator containing bipyridinium nitrogen, characterized in that: Includes steps: Providing an OPBI solution and a C2N solution; The OPBI solution and the C2N solution are mixed to obtain an OPBI@C2N mixed solution; The OPBI@C2N mixed solution is coated on a substrate, and the solvent in the OPBI@C2N mixed solution is removed to obtain a lithium ion battery separator containing bipyridine nitrogen.

2. The method for preparing a lithium ion battery separator containing bipyridinium nitrogen according to claim 1, characterized in that: The solvent of the C2N solution and the solvent of the OPBI solution are jointly selected from one or more of N-methylpyrrolidone, dimethyl sulfoxide, and N,N-dimethylacetamide.

3. The method for preparing a lithium ion battery separator containing bipyridinium nitrogen according to claim 1, characterized in that: In the OPBI@C2N mixed solution, the mass proportion of C2N is 0.2%-0.9%.

4. The method for preparing a lithium ion battery separator containing bipyridinic nitrogen according to claim 1, characterized in that: In the preparation process of C2N, a dichloromethane solution of a precursor HAT-CN is mixed with NaCl and then sintered at a high temperature under the protection of an inert gas.

5. The method for preparing a lithium ion battery separator containing bipyridinic nitrogen according to claim 4, characterized in that: The high temperature is 400-1000°C.

6. The method for preparing a lithium ion battery separator containing bipyridinic nitrogen according to claim 1, characterized in that: The mixing process is to continue stirring at room temperature for 15-24 hours.

7. The method for preparing a lithium ion battery separator containing bipyridinic nitrogen according to claim 1, characterized in that: The method for removing the solvent in the mixed solution is: placing the substrate coated with the mixed solution in anhydrous methanol for immersion treatment, and the immersion treatment is standing at room temperature for 8-15 minutes.

8. A lithium ion battery separator containing bipyridinic nitrogen, characterized in that: The lithium ion battery separator containing bipyridinium nitrogen is prepared by the preparation method according to any one of claims 1 to 7, and the microscopic pore structure of the separator is composed of regular, dense and orderly finger-like pores and sponge-like pores.

9. The lithium ion battery separator containing bipyridinic nitrogen according to claim 8, characterized in that: The thickness of the lithium ion battery separator containing bipyridinium nitrogen is 25-40 microns.

10. A lithium ion battery, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet and a lithium ion battery separator containing bipyridinyl nitrogen as claimed in any one of claims 8 to 9; the lithium ion battery separator containing bipyridinyl nitrogen is located between the positive electrode sheet and the negative electrode sheet.